Starsky & Hutch - Blinn, William; O'Brien, John, 1963-; Phillips, Todd, 1970-; Armstrong, Scot.; Stiller, Ben, 1965-; Wilson, Owen, 1968-; Vaughn, Vince; Lewis, Juliette; Williamson, Fred.; Bateman, Jason; Penn, Christopher; Snoop Dogg, 1972-; et al. (Burbank, CA : Warner Home Video, 2004)
Set in the 1970s Bay City, two undercover police detective, Ken "Hutch" Hutchinson and Dave Starsky, always seem to get the toughest cases from their boss, Captain Dobey. They rely on their street informer Huggy Bear and race to the scene of the crimes in their souped-up 1974 Ford Torino hot rod. The two are on their first big case which involves a former college campus drug dealer who has gone on to become a white collar criminal dealing in a new "undetectable" form of cocaine.
Based on the characters created by William Blinn.
Special features: audio commentary with director Todd Phillips; deleted scenes; East eggs: Vince's bits for the kids: Vince discusses his thoughts on DVD special features; "Last look special-documentary spoof" featurette; "Fashion fa sizzle wit Huggy bizzle" fashion insights with Snoop Dogg; theatrical trailer; gag reel.
Director of photography, Barry Peterson ; editor, Leslie Jones ; music, Theodore Shapiro ; costume designer, Louise Mingenbach ; production designer, Edward Verreaux.
Ben Stiller, Owen Wilson, Vince Vaughn, Juliette Lewis, Fred Williamson, Jason Bateman, Chris Penn, Carmen Electra, Amy Smart, Snoop Dogg.
MPAA rating: PG-13; for drug content, sexual situations, partial nudity, language and some violence.
DVD, Region 1, full screen (1.33:1) presentation; Dolby Digital, DTS, SDDS.
Keywords: Detectives -- Drama; Criminal investigation -- Drama; Drug dealers -- Drama; Films for the hearing impaired; Feature films